2007
DOI: 10.2337/db07-0238
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Hyperinsulinemia Has No Detectable Effect on Access of Macromolecules to Insulin-Sensitive Tissues in Healthy Humans

Abstract: OBJECTIVE-Physiologically elevated insulin concentrations promote access of macromolecules to skeletal muscle in dogs. We investigated whether insulin has a stimulating effect on the access of macromolecules to insulin-sensitive tissues in humans as well.RESEARCH DESIGN AND METHODS-In a randomized, controlled trial, euglycemic-hyperinsulinemic clamp (1.2 mU ⅐ kg Ϫ1 ⅐ min Ϫ1 insulin) and saline control experiments were performed in 10 healthy volunteers (aged 27.5 Ϯ 4 years, BMI 22.6 Ϯ 1.6 kg/m 2 ). Distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Previous studies suggest that the effect of insulin on blood flow is an important component of its stimulation of glucose uptake (20), although other studies did not reproduce this result (21)(22)(23). In our study, BF was increased in the forearm muscles of HR in both the fasting and postprandial states confirming previous observations (11).…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies suggest that the effect of insulin on blood flow is an important component of its stimulation of glucose uptake (20), although other studies did not reproduce this result (21)(22)(23). In our study, BF was increased in the forearm muscles of HR in both the fasting and postprandial states confirming previous observations (11).…”
Section: Discussionsupporting
confidence: 85%
“…The authors in the later study proposed that the observed diet-induced defect in stimulation of tissue perfusion contributes to the development of peripheral insulin resistance (43). However, in a recent report, physiological hyperinsulinemia was found to have no detectable effect on access of inulin to insulin-sensitive tissues in healthy humans (183). The significance of this difference between dogs and humans remains to be explained.…”
Section: Insulin-mediated Increases In Microvascular Perfusionmentioning
confidence: 99%
“…82 and 120). To date, there has been only one study where the notion that insulin increases delivery to muscle has been challenged (183), but that study specifically examined inulin distribution volume and not microvascular perfusion. This reviewer is unaware of findings that directly dispute that insulin-mediated capillary recruitment occurs or that capillary recruitment is impaired in insulin-resistant states.…”
Section: Insulin-mediated Increases In Microvascular Perfusionmentioning
confidence: 99%
“…Open flow microperfusion can be used to monitor concentrations by sampling substances regardless of size and lipophilicity . Cerebral open flow microperfusion (cOFM) has been optimized for application in the brain and allows sampling without affecting the integrity of the BBB .…”
Section: Introductionmentioning
confidence: 99%